(Invited) Advanced Transistors for High Frequency Applications. (24th April 2020) - Parvais, Bertrand; Peralagu, Uthayasankaran; Vais, Abhitosh; Alian, AliReza; Witters, Liesbet; Mols, Yves; Walke, Amey; Ingels, Mark; Yu, Hao; Putcha, Vamsi; Khaled, Ahmad; Rodriguez, Raul; et al.
Abstract : Downscaling CMOS technology has allowed the integration of high-speed transceivers on silicon chips, but high-power amplifiers rely on III-V technologies to deliver the power and efficiency levels required by modern radios. In this work, we explore two routes to enable the fabrication of compound semiconductor devices on a large-scale manufacturable Si platform. In the first route, we report on Al(Ga, In)N HEMTs, MISHEMTs and MOSFETs integrated on 200 mm Si wafers using Au-free processing in standard Si CMOS tools. In the second route, we demonstrate GaAs/InGaP HBTs grown on a 300 mm Si substrate using Nano-Ridge Engineering (NRE) combined with aspect ratio trapping (ART). We provide insight on the potential of these new technologies for the design of advanced front-end modules, including performance trade-offs, modelling and reliability challenges.